Management of root resorption on anterior tooth after fixed orthodontic treatment - Cinitra Anindya; Kun Ismiyatin; Gavrilla Wibisono; Nindhira Puspita; Alia Hani Murad; Kamila Tri Nasywarani (Conservative Dentistry Journal, 2026)
Background: The application of orthodontic mechanical forces on maturing teeth can disrupt Hertwig’s epithelial root sheath (HERS) morphology and induce orthodontically induced inflamatory root resorption (OIIRR), characterized by apical bending and decreased cell proliferation, resulting in a shortened root with an open apex that necessitates apexification to stimulate calcified barrier formation in cases of necrotic pulps. Purpose: This case report aims to describe apexification case on tooth 22 with Mineral Trioxide Aggregate (MTA). Case(s): A 27-year-old female patient presented to the Clinic of Conservative Dentistry, University Airlangga Dental Hospital, with a chief complaint of cavities in her upper front tooth so that the patient felt shy when smiling. That tooth felt uncomfortable when biting and she wanted to treat her tooth. Case Management: The root canal exploration revealed a gauging size of 50, confirming the presence of a wide apical foramen. This finding is consistent with the radiographic examination, which shows that tooth 22 with open apex. The treatment plan is endodontic treatment in the form of apexification using Mineral Trioxide Aggregate (MTA) material. The obturation technique was performed using thermoplastic (backfill) and the fixed restoration using a fiber post with composite resin. Conclusion: In this clinical case, based on a gauging size of 50 and radiographic findings showing an open apical foramen, the patient was treated with apexification using MTA to create an apical plug, followed by a post insertion and a composite resin restoration.